El Berlín de Ayala - Ingenschay, Dieter (Revista de Filología Alemana, 2010)
What did Berlin -"strange city"- mean to a young Spaniard at the end of the Weimar years, during the roaring twenties, when Ayala went there to study Law? How did he experience a culture that differed so much from his own at that time? Provided with letters of recommendation, he was accepted in Berlin academic circles where he met Etelvina Silva Vargas, his first wife, became friends with the German scholar Walter Pabst, and finally witnessed the rise of Nazism. Once the war was finished, he returned a number of times to Germany, but to Berlin he just returned once. The author acquaints the reader with this and other episodes in some of the chapters of his Recuerdos y olvidos ("Mi Berlín", "La universidad alemana ", "Me asomo a la Alemania nazi"). Moreover, the Berlin of the 1920s is the exotic setting of two of very remarkable stories by Ayala ("Erika ante el invierno" and "San Silvestre "). This article shows how Ayala’s stay in Berlin meant much more than just a fleeting episode, but rather left important traces in both the life and the work of the Granadian author.